European Society of Coloproctology consensus on the surgical management of intestinal failure in adults. (8th June 2016) - ,; Vaizey, C. J.; Maeda, Y.; Barbosa, E.; Bozzetti, F.; Calvo, J.; Irtun, Ø.; Jeppesen, P. B.; Klek, S.; Panisic‐Sekeljic, M.; Papaconstantinou, I.; Pascher, A.; et al.
Abstract: Intestinal failure (IF) is a debilitating condition of inadequate nutrition due to an anatomical and/or physiological deficit of the intestine. Surgical management of patients with acute and chronic IF requires expertise to deal with technical challenges and make correct decisions. Dedicated IF units have expertise in patient selection, operative risk assessment and multidisciplinary support such as nutritional input and interventional radiology, which dramatically improve the morbidity and mortality of this complex condition and can beneficially affect the continuing dependence on parenteral nutritional support. Currently there is little guidance to bridge the gap between general surgeons and specialist IF surgeons. Fifteen European experts took part in a consensus process to develop guidance to support surgeons in the management of patients with IF. Based on a systematic literature review, statements were prepared for a modified Delphi process. The evidence for each statement was graded using Oxford Centre for Evidence‐Based Medicine Levels of Evidence. The current paper contains the statements reflecting the position and practice of leading European experts in IF encompassing the general definition of IF surgery and organization of an IF unit, strategies to prevent IF, management of acute IF, management of wound, fistula and stoma, rehabilitation, intestinal and abdominal reconstruction, criteria for referral to a specialist unit and intestinal transplantation.